Masyarakat SIMULASI DAN SIMULAKRA JEAN BAUDRILLARD DALAM DINAMIKA BUDAYA KONSUMSI BERLEBIHAN MASYARAKAT POSTMODERN - TRI PUSPA AGUSTINA; Rachel Meriah Piouli M; Vieronica Varbi Sununianti; Istiqoma; Deni Aries Kurniawan (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2025)
This research analyzes the phenomenon of hyperconsumption in modern society based on Jean Baudrillard's theory of simulation and simulacra. The formulation of the problems raised are: How does the process of simulation and simulacra contribute to excessive consumption, and what are the theoretical and practical implications for postmodern society. This research uses a literature study approach (narrative review), namely by analyzing relevant scientific writings, books, and journal articles. The results show that media, advertising, and digital technology contribute to creating false needs and images that transcend reality, resulting in hyperreality and implosion of meaning. This encourages people to continue consuming to fulfill identity and recognition needs, not functional needs. This research also found the need for critical awareness and a broader theoretical approach to create a more humane, just and appropriate consumption model.